Craniofacial Distraction - McCarthy, Joseph G. (Springer International Publishing : Imprint: Springer, 2017)
This book, edited by a leading pioneer of craniofacial distraction, summarizes the progress achieved in the field in a way that will serve the needs of the practicing clinician. All components of the craniofacial anatomy are covered and all topics are discussed in depth: clinical and anatomic pathology, diagnostic studies, treatment protocols, preoperative planning (including the latest virtual programs), device selection, operating room technical considerations, postoperative management, and intermediate/long-term follow-up. Relevant and timely studies from the literature are cited. The book is excellently illustrated, with many patient photos, radiographs, and drawings. Craniofacial Distraction will be a superb, up-to-date resource for a wide range of practitioners, including maxillofacial surgeons, craniofacial surgeons, plastic surgeons, head and neck surgeons, pediatric surgeons, orthodontists, prosthodontists, and pedodontists.
Keywords: Dentistry.; Medicine.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books